Optimizing BT-1804 Product Quality with Six Sigma Approach - Apriani, Ratna Agil; Basuki, Demas Emirbuwono; Handayani, Dwi; Wibowo, Latifah Fitri Nuraida (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
PT. Bakrie Autoparts produced BT-1804 products for 12 months, and of the 9537 units produced, there were 3572 product defects with various types of defects. Therefore, Six Sigma with DMAIC is used to minimize defect problems. In stages, define used Critical to Quality (CTQ), where 16 types of potential defects were found in the BT-1804 product. At stage Measure, the Pareto diagram measures the highest frequency of defects and the improvements needed. At stageAnalyze used the Fishbone Diagram, where this method focuses on repairing 1 type of defect in BT-1804, which is the type of machining defect that is the dominant defect. At stageImprove, correcting the root of the problem with FMEA (Failure Mode and Effect Analysis), where it was found that inaccurate machine settings had the highest RPN value of 100. So, suggestions were given by providing knowledge in the form of training related to production mechanisms and providing supervision of operator performance during the machine setting process. Keywords: Quality Improvement, Six Sigma, DMAIC; Failure Mode and Effect Analysis